1986
DOI: 10.1159/000132283
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenicity in somatic cell hybrids

Abstract: An analysis for cosegregation of chromosomes and tumorigenicity in 52 hybrids of human diploid × D98AH2 human carcinoma-derived cells reveals the consistent presence of four copies of chromosome 11 in all nontumorigenic hybrids (two from each of the parental cells) and a consistent loss of one or two copies of the 11 in all tumor cells derived from tumorigenic hybrids that grow in nude mice. In our earlier study, assays with restriction fragment length polymorphic (RFLP) markers for the cell parent origin of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…A similar chromosome dosage dependency was observed in the suppression of tumorigenicity in hybrids derived from the human carcinoma cell line D98AH2 (29) and the fibrosarcoma cell line HT1080 (30). In the latter, the relative number of chromosome 1 alleles bearing the normal vs. activated N-ras gene was suggested to play a critical role in the suppression of tumorigenicity.…”
Section: Resultssupporting
confidence: 64%
“…A similar chromosome dosage dependency was observed in the suppression of tumorigenicity in hybrids derived from the human carcinoma cell line D98AH2 (29) and the fibrosarcoma cell line HT1080 (30). In the latter, the relative number of chromosome 1 alleles bearing the normal vs. activated N-ras gene was suggested to play a critical role in the suppression of tumorigenicity.…”
Section: Resultssupporting
confidence: 64%
“…T h e presence of one or more tumor suppressor genes on human chromosome 2 was first suggested by Klinger and Kaelbling (1986). Their study revealed that tumorigenicity was suppressed in somatic cell hybrids between human cervical carcinoma cells (HeLa) and normal human fibroblasts, whereas the hybrids reexpressing tumorigenicity concomitantly lost chromosomes 2 and 1 1 derived from the normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observations of melanoma suppression by a particular chromosome, we proposed the appearance of human melanoma, retinoblastoma, Wilms' tumor, phaeochmmocytoma, and tumors of breast, ovaries, stomach, and colon many years ago as loss or impairment of tumor genespecific regulatory genes . Today, the formal similarity of the phenomenon of suppression or permission of tumorigenicity by a particular chromosome observable in the animals themselves, to that observable in human cell lines, e.g., chromosome 6 in melanoma, chromosome 11 in cervical carcinoma, W i l m s ' tumor, and fibrosarcoma, chromosome 17 in neuroblastoma and breast carcinoma, chromosome 18 and 5 in colorectal cancer (Stanbridge, 1976(Stanbridge, , 1989(Stanbridge, , 1990Klinger, 1982;Klinger and Kaelbling, 1986;Huff et al, 1988;Cropp et al, 1990;Dracopoli et al, 1985;Kugoh et al, 1990;Fearon et al, 1990;'hnaka et al, 1991;Weissmann et al, 1987; see reviews in Bock and Marsh, 1989), is self-evident and reveals formally a problem of gneral cancerology. Moreover, allele losses have recently been defined in human tumors by DNA studies of the site of the loss (Stanbridge, 1989; Ponder, Large interactive technical as well as living systems or parts of them, inherently evolve toward a critical state in which an obviously minor event, like incidental loss of a controlling element, can lead to a breakdown.…”
Section: Reflections and Implicationsmentioning
confidence: 99%